Human resources management, a non-financial benefit of venture capital - Antonio Gledson de Carvalho (Universidade de São Paulo, 1999)
This article addresses the question of whether venture capital brings non-financial benefits to the firms it funds. I propose that venture capital adds value because venture capitalists are able to transfer information about senior managers across firms and time. For this transfer to exist on a significant scale, it is necessary that venture capitalists operate a network, within which they are involved in locating and relocating managers. Results obtained through a survey of venture capitalists based in the US confirm the existence of such a network: The majority of the respondents affirm that it is common for them 1) to act on suggestions from their colleagues when hiring managers; and 2) to recommended managers to other venture capitalists. Econometric analysis shows that the factors relevant to explain the intensity with which venture capitalists network include: 1) the value of the information transmitted though the network; 2) the degree of risk that venture capitalists attribute to their investments; 3) how difficult venture capitalists find it to entice executives to manage firms funded with their capital; and 4) the gains that the venture capitalists who suggest managers can obtain when enticing managers to accept job offers.